Adding to complexity: How a revived use of psychological theory can benefit attempts to stimulate change in patterns of personal travel - Ellingsgaard, Hannah Villadsen (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
This paper seeks to broaden the view of psychological theory in research in behavioral change in transport as a way of responding to climate change. In recent years the use of psychological theory has been increasingly criticized for supporting individualizing, atomized and simplistic perspectives on change (Watson, 2012; Geels, 2012; Chatterton & Wilson, 2014; Schwanen, Banister & Anable, 2011). While welcoming this important and justified critique this article seeks to capture and defend the fundamental insights that these models have contributed to. The aim is to separate the baby from the bathwater and point to how theories of individual behavior and aggregate perspectives such as theories of practice can inform each other and result in enhanced methods. First the use of psychological theory in journal articles on behavioral change in transport is reviewed. A comprehensive theoretical review is used to point to strengths and weaknesses in current approaches. Lastly an informed eclectic approach is advocated by proposing an operational framework that draws on established theories of attitude and behavioral choice as well as cultivating a better understanding of practices involved in personal travel.